Analyzing the Role of Corporate Sector in Achieving SDGs through Corporate Social Responsibility Initiatives in Punjab, Pakistan - Mirza, Hatim; Zaighum, Zeeshan; Rasool, Farasat (Journal of Peace, Development and Communication, 2021)
The contribution of the corporate sector in the field of development has had a presence since a long time, but it was merely analyzed in the context of development. This study analyses the corporate sector’s role in achieving SDGs through CSR initiative in Punjab/ Pakistan. This research is a qualitative approach through in-depth interviews with executive level representatives from both the corporate and public sector. Moreover, the research questions explored areas like CSR approaches and alignment of corporate sector with SDGs, nature of CSR initiatives, the existing challenges and relevant legal frameworks in Punjab (Pakistan). The results reflected that currently reactive CSR approach remains prevalent among the corporate sector; moreover, there are coordination barriers between the public and corporate sector, in terms of communicating the SDGs. It has also been found that there is a lack of policy framework thus creating more governance related issues to accomplish SGDs.